Increasing the Revenue Through Digital Marketing: A lesson learned from a Small Business Enterprise Run by Volunteers of Community with Disability - Herawati, Vita Dian; Rahmaningtyas, Anindya; ulfatirrohman, Atikah Itsna Z; Pratiwi, Hildayanti Eka; Indriawan, Toni; Fiddien, Gigih Dutyama; yang, Lu; Taki, Sarah; Suswardany, Dwi Linna (Universitas Muhammadiyah Surakarta, 2022)
Digital marketing has become increasingly important and needed in the New Normal, especially for small industries such as Amor Ethnic. Amor Ethnic is a self-help group/community with disabilities with businesses in the form of hands and feet crafts using macrame materials. This micro-enterprise was affected by the Covid-19 pandemic, so there were no sales for four months. Therefore, expansion of market reach must be done immediately. Amor Ethnic has used Instagram for marketing, but it did not use Instagram marketing optimally. The purpose of this community service was to improve the knowledge and skills of the Amor Ethnic community in using Instagram for marketing and to increase their business turnover. Marketing 3.0, selecting a caption that reflects FAITH (Feel Assurance in The Heart), was chosen as the uniqueness of Amor Ethnic's marketing approach. Training and mentoring methods were conducted through the WhatsApp and Google Meet applications. The topics were product photography, photo editing, ads and feed design, preparation of Instagram feeds, use of Instagram Ads, analysis of Instagram Ads insight data, and preparation of content strategies to maximise the use of Instagram. Evaluation was using pretest and posttest. The results showed there were improved skills in implementing digital marketing using Instagram. The improvement was seen in improved quality of product photos, Instagram design, followers, profile visits, reach of Instagram accounts, and increased customer orders and turnover.